Property (Ω ̅ ) and holomorphic functions with values in a pseudoconvex space having a Stein morphism into a complex Lie group, - Thai Thuan Quang; Nguyen Minh Ha (My University, 1995)
Property (Ω ̅ ) and holomorphic functions with values in a pseudoconvex space having a Stein morphism into a complex Lie group,
Keywords: Pseudoconvex space; Ω property; Stein morphism